PENATAAN ANCAMAN EKONOMI SEBAGAI BAGIAN DARI KEADAAN BAHAYA DI INDONESIA - Adhari, Agus (Dialogia Iuridica, 2020)
This article aims to analyze economic threats in times of emergency. Threats in the modern era consist of many types, and most of it dominated by nonmilitary threats such as disasters and social conflicts. However, apart from these two threats, economic threats also have the same effect on national security. The Indonesian government has been responded to economic threats differently since 1998 when it faced an economic crisis, then when it faced the threat of an economic recession due to the impact of the Covid-19 Pandemic. The difference in ways of responding to economic threats is because Indonesia does not regulate economic threats as threats of state of emergency, so policies to respond to economic threats are limited by rules that cannot be violated. Therefore, this article will discuss the arrangement of economic threats in times of emergency. As a result, by regulating an economic threat as part of a state of emergency, the government has the power to shape economic policy by deviating from the provisions that apply under normal conditions. The economic emergency arrangement is carried out by regulating economic threats as part of a state of emergency through the law, then also regulates the scope of the President’s powers, the organ of exercising power, time limits, and forms of responsibility.